Measurement in Correctional Health Research: Unique Challenges and Strategies for Enhanced Rigor. (July 2019) - Prost, Stephanie Grace; Kennedy, Stephanie; Peck, Jennifer; Bouchaud, Mary T.; Shelton, Deborah
It is essential to identify valid and reliable measurement strategies to enhance accurate, comprehensive, and meaningful health assessment and evaluation to improve health outcomes among justice-involved and incarcerated populations. This article identifies and describes three primary challenges related to measurement in correctional health care and makes four recommendations for enhanced measurement rigor from a social justice perspective. First, incorporate incarcerated persons into the measurement research process; second, enhance psychometric investigation in correctional health settings; third, increase the collection of individual-level, health-related data from incarcerated populations; and fourth, create and maintain centralized databases and comprehensive codebooks to promote data sharing.